Pengaruh Media Papan Tusuk Huruf Terhadap Kemampuan Membaca Dengan Menggabungkan Huruf Vokal dan Konsonan Siswa kelas 1 SDN 101744 Desa Kelambir - Mastari Ramadhani; Syarifah Ainun Harahap; Mulkan Andika Situmorang (CV. ITTC INDONESIA, 2024)
This study aims to improve the quality of the use of learning media in the teaching and learning process of students. With this learning media, students are motivated and interested in exploring the learning taught by educators in the classroom. The researcher used an experimental researchtype by making a media and collecting data on the number of students in grade 1 SD Negeri 101744 Desa Klambir, as well as conducting tests, interviews and documentation to educators and school principals. The data used by the researcher is the research sample and the distribution of pre-test and post-test. taken from 23 students in class 1 A (experimrntal class) and 20 studens in class 1 B (control class), the result of the study resulted in the experimental class pre-test 480,5 and control class pre-test 416 from all students, then the results from research from research post-test experimental class 190,5 and post-test control class 169,5 of all students.